2020
DOI: 10.14338/ijpt-20-00022.1
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Proton Patients in the COVID-19 Pandemic: Recommendations from The New York Proton Center

Abstract: It has been well documented from the early days of the 2019 novel coronavirus (COVID-19) pandemic that patients with a diagnosis of cancer are not only at higher risks of contracting a COVID-19 infection but also at higher risks of suffering severe, and possibly fatal, outcomes from the infection. Given that the United States has the greatest number of positive coronavirus cases, it is likely that many, if not all, radiation oncology clinics will be faced with the challenge of safely balancing a patient's risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Similarly, Chhabra et al developed an internal algorithm that helped maintain patients’ treatment volume while keeping the rate of COVID-19 infection acceptable. Importantly, this algorithm considers treatment-related, tumor-related, and patient-related characteristics in order to guide the safest decision ( Chhabra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chhabra et al developed an internal algorithm that helped maintain patients’ treatment volume while keeping the rate of COVID-19 infection acceptable. Importantly, this algorithm considers treatment-related, tumor-related, and patient-related characteristics in order to guide the safest decision ( Chhabra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a response to the severe COVID-19 crisis in the SAUCCC, multidimensional adjustments of radiotherapy have continuously updated to deal with the negative impact on the cancer treatment during the COVID-19 pandemic ( 10 , 17 19 , 23 , 24 , 28 , 34 , 42 , 43 ). The role of radiotherapy in the treatment of liver cancer has undergone a significant shift due to the pandemic ( 10 , 18 ), which is necessary for similar dilemmas in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, photon and proton SABRs are the feasible alternative strategies to CIRT in the regions without CIRT resource ( 18 20 , 33 ). In order to achieve the above advantages of CIRT, hypofractionation regimens for photon and proton radiotherapy should be adequately utilized to shorten treatment schedules for liver cancer patients in the SAUCCC when feasible and appropriate ( 18 , 33 , 34 ). Compared with photon, proton radiotherapy has the superiority of Bragg peak that allows for the pinpoint delivery of maximum sharp energy deposition to tumors while minimizing toxicity to the surrounding noncancerous tissues and organs.…”
Section: Radiotherapy For Liver Cancer In the Covid-19 Eramentioning
confidence: 99%
“…Experience from other centers in areas of high community spread [ 6 ] have suggested that maintaining adequate RTT staffing would be the most critical component of maintaining our ability to deliver proton therapy during the pandemic. In mid March, we developed a phased model of RTT staffing that would allow us to gradually ramp down the number of RTTs at the PTC ( Table ).…”
Section: Ptc-specific Responsementioning
confidence: 99%